2011
DOI: 10.1111/j.1742-1241.2011.02694.x
|View full text |Cite
|
Sign up to set email alerts
|

Are the risk factors listed in warfarin prescribing information associated with anticoagulation-related bleeding? A systematic literature review

Abstract: Warfarin significantly reduces thromboembolic risk, but perceptions of associated bleeding risk limit its use. The evidence supporting the association between bleeding and individual patient risks factors is unclear. This systematic review aims to determine the strength of evidence supporting an accentuated bleeding risk when patients with risk factors listed in the warfarin prescribing information are prescribed the drug. A systematic literature search of MEDLINE and Cochrane CENTRAL was conducted to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
0
10
1
2
Order By: Relevance
“…[19][20][21][22] In particular, warfarin is underutilized in patients with atrial fibrillation with co-morbid substance abuse, 23 but evidence to support this decision has been sparse. 24 , 25 A recent systematic review found a statistically significant increase in hemorrhages in alcohol abusers in less than half of the studies and reported overall strength of the evidence as low. 25 Poorer anticoagulation control in substance-abusing patients is concerning, since improved control is associated with fewer adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] In particular, warfarin is underutilized in patients with atrial fibrillation with co-morbid substance abuse, 23 but evidence to support this decision has been sparse. 24 , 25 A recent systematic review found a statistically significant increase in hemorrhages in alcohol abusers in less than half of the studies and reported overall strength of the evidence as low. 25 Poorer anticoagulation control in substance-abusing patients is concerning, since improved control is associated with fewer adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant risk reductions are also observed for the other warfarin indications [5]. Although it has a significant thromboembolism risk reduction, incorrect warfarin dosing can be associated with thromboembolic events (in the case of underdosing) or bleeding complications (in the case of overdosing) [6]. Warfarin is the first cause of emergency room visits for adverse drug events in older adults in the USA [7].…”
Section: Introductionmentioning
confidence: 96%
“…In this issue of the International Journal of Clinical Practice , Chen et al. report the results of a systematic review to determine the strength of evidence supporting an accentuated bleeding risk when patients with risk factors listed in the warfarin prescribing information (in terms of contraindications, warnings, and precautions) are prescribed warfarin (7). Risk factors for bleeding include ‘haemorrhagic tendencies, blood dyscrasias, characteristics listed in the black box warning, unsupervised patients with senility or alcoholism, severe heart disease, and anaemia’ (7).…”
mentioning
confidence: 99%
“…The review by Chen et al. (7) is comprehensive and includes 35 articles published between 1988 and 2009, from 34 unique studies (two post hoc analyses of randomised controlled trials, 11 prospective observational studies, 18 retrospective observational studies, two mixed prospective and retrospective studies, and one study of unclear study design). The total sample size was 148,443 patients (80–66,988 within individual studies), with a median duration of follow‐up of 1247 patient‐years (221–133,976 patient‐years).…”
mentioning
confidence: 99%
See 1 more Smart Citation